Treatment of chronic hepatitis B: options, monitoring, special cases and adverse effects - Litwin, Mateusz; Mikosińska, Agnieszka; Parys, Jakub; Kałuziak, Patrycja; Witek, Aleksandra; Kaźmierczak, Martyna; Jesionek, Stanisław; Jajczak, Marta; Mossakowski, Maciej (Journal of Education, Health and Sport, 2025)
Introduction: Hepatitis B remains a significant clinical issue. Despite the availability of effective vaccines, the world is still not free from this problem. Chronic hepatitis B virus (HBV) infection affects approximately 296 million people worldwide and is the leading cause of cirrhosis and liver cancer globally. HBV-related cirrhosis resulted in an estimated 331,000 deaths in 2019, and it is estimated that the number of deaths from HBV-related liver cancer in 2019 was 192,000, an increase from 156,000 in 2010. The rate of vaccination is particularly unsatisfactory in low-income countries, but even in high-income countries, the issue of hepatitis B has not been completely eradicated. Aim of the study: The aim of this paper is primarily to systematize knowledge regarding the natural course of HBV infection and therapeutic options for chronic hepatitis B, both in adults and children. It also aims to highlight the principles of monitoring pharmacotherapy. The paper also describes therapeutic possibilities in special cases, such as pregnancy, liver transplantation, and the initiation of immunosuppressive therapy. Attention is also given to the potential adverse effects of pharmacotherapy. Conclusions: As hepatitis B infection continues to pose a significant global health challenge and remains the leading cause of liver cirrhosis and hepatocellular carcinoma, it is essential to review the available treatment options for this condition. Even in Europe, where vaccination coverage has reached high levels, cases of hepatitis B are still detected, often incidentally. This review aims to provide an in-depth analysis of therapeutic approaches for chronic hepatitis B, considering factors such as patient age, clinical status, and liver fibrosis stage. Additionally, it emphasizes the importance of monitoring treatment efficacy and safety, while also addressing the potential adverse effects associated with antiviral therapy.